KINERJA APARATUR TERHADAP PELAYANAN PUBLIK DI KANTOR DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Asri Jide (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
This study aims to determine the performance of the apparatus in the Timoreng Panua Village office, public services at the Timoreng Panua Village office and the performance of the apparatus for public services in the Timoreng Village office, Panua, Panca Rijang Subdistrict, Sidenreng Rappang District. The population in this study was 547 heads of households whose sampling was used, namely probability sampling, with random sampling using a Yount formula of 10% with a sample of 55 heads of families, this study used a quantitative descriptive method. Data collection techniques used through observation, questionnaires, and documentation. Data analysis techniques used were frequency tabulation analysis, and linear regression analysis using SPSS 21.0 for windows.The results of this study indicate that the average percentage of apparatus performance in the Timoreng Village office in Panua, Panca Rijang District, Sidenreng Rappang Regency was 56.25% with a fairly good category, public services in the Timoreng Panua Village office in Panca Rijang District, Sidenreng Rappang District at 65.52% with a good category of apparatus performance on public services in the Timoreng Panua Village office, Panca Rijang District, Sidenreng Rappang Regency, at 20.2% with no effect category.